Procedural tactics in the investigation of property damage to a law enforcement officer (Law and Safety, 2023)
One of the structural components of the forensic methodology for investigating intentional destruction or damage to property of a law enforcement officer is the specific tactics of certain investigative (detective) actions. The complexity of their conduct, as well as their significant effectiveness in collecting evidence of a person's guilt and in clarifying the circumstances of the said criminal offence, necessitate a thorough study on this issue. Considering this, the purpose of the study is to determine the tactical and organisational features of investigative (detective) actions during the investigation of intentional destruction or damage to property of a law enforcement officer.It has been established that scene examinations during the investigation of intentional destruction or damage to property of a law enforcement officer are challenging, time-consuming, require the use of various types of special knowledge and skills, and also involve the use of a large number of technical and forensic tools, so the investigator is obliged to treat their planning, preparation and conduct responsibly and ensure their implementation in accordance with the principles of legality, science, comprehensiveness, completeness, thoroughness, etc. It has been determined the main tactical tasks to be solved during the inspection of the place of destruction or damage to the property of a law enforcement officer.It has been substantiated that the interrogation tactics and techniques used by the prosecution must comply with the provisions of the current criminal procedure legislation. Given that in the category of crimes under study, the victim is a law enforcement officer or his/her close relative, this should not influence the prosecution representative and lead to a biased attitude towards the suspect or witness who is trying to avoid giving full and objective testimony.Based on the analysis, it has been established that the most correct approach is to interrogate the victim first, even in an investigative situation when a person involved in a criminal offence is detained at the scene of the crime. It has been provided a list of circumstances that should be clarified during the interrogation of a victim, witness or suspect.It has been found that the tactical techniques which should be used during investigative experiments in the investigation of intentional destruction or damage to property of a law enforcement officer are: repeated conduct of experiments and control over their implementation; creation of an environment which will facilitate the provision of as much detailed information as possible about the circumstances of criminal offences; asking questions to a participant of an investigative experiment with a view to detailing his/her explanations and evaluating the answers; the use of models, application of scientific and technical means and involvement of specialists with special knowledge in the relevant field of science; application of technical means of recording, in particular, continuous video recording.
Keywords: pre-trial investigation; investigative (detective) action; tactics; scene inspection; interrogation; investigative experiment; damage or destruction of property.